THE IMPACT OF STRATEGIC FORESIGHT ON ACHIEVING ORGANIZATIONAL FLEXIBILITY: A FIELD STUDY FOR A GROUP OF LEADERS IN THE NORTH OIL COMPANY - Assistant Lecturer Walid Dahham Abd; Lecturer Dalal Saleh Mahdi; Assistant Lecturer Mazhar Ahmed Khalaf (Scholars Digest Publishing, 2023)
The main purpose of this study is to investigate the effect of strategic foresight on creating dynamic capabilities for organizational flexibility and rational decision-making in the North Oil Company, and to analyze the correlation and influence relationships between the research variables. The approach followed in this research is descriptive and analytical by presenting the conceptual sequence of the research variables, and working on analyzing the data collected from the researched field. The data of this research was collected using the method of intentional sampling by targeting the leaders of the employees of the company, and building a questionnaire form prepared by the researchers using the indicators and research questions based on a set of models and previous studies. The opinions of professors and experts were used to validate this questionnaire, and Cronbach's alpha was used for reliability which was set to 0.943. SPSS program was used to test the hypotheses of this research. The research data was collected by 63 leaders in the company who have knowledge in the field of strategic planning, marketing, production and human resource management, according to the limited statistical community in the company.
Keywords: Strategic foresight, organizational flexibility.